Implementation of Revocation of Travel Business Permits Due to Not Periodic Testing in Pekanbaru City Based on Law Number 22 Year 2009 concerning Traffic and Transportation Road Transport - Dasmon Simanjuntak (Universitas Muhammadiyah Sumatera Utara, 2022)
In order to ensure the feasibility of passenger or goods vehicles (angkot, buses, trucks) on the road, the government should supervise. The supervision carried out is in the form of periodic tests carried out by the government, especially the ministry of transportation, which is clearly regulated in Law Number 22 of 2009 concerning Junto Road Traffic and Transportation Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 133 of 2015 concerning Periodic Testing of Motorized Vehicles (Permenhub) PBKB). In Article 49 paragraph (1) of Act No. 22 of 2009 it is stated that imported, manufactured and/or assembled Motorized Vehicles, trailers, and patch trains that are imported, manufactured and/or assembled in the country to be operated on the road must be tested. The implementation of the revocation of travel business permits due to not having periodic tests in Pekanbaru City is not implemented properly, there are still many travellers who are not tested regularly and are not given sanctions. The obstacles in implementing the revocation of travel business licenses due to not having periodic tests in Pekanbaru City are due to the low legal awareness of travel owners, lack of testing staff and ability to test and equipment facilities that do not support. Efforts to overcome obstacles in implementing the revocation of travel business licenses due to not having periodic tests in Pekanbaru City are by making policies and proposing additional testing staff and carrying out maintenance of testing facilities and equipment